Joaquín ÁLVAREZ BARRIENTOS, "El actor borbónico (1700-1801)", Madrid, Asociación de Directores de Escena de España, 2019, 512 págs. - Escalante Varona, Alberto (Cuadernos de Estudios del Siglo XVIII, 2020)
SIN RESUMEN